Process and nano-ZSM-5-based catalyst formulations for cracking crude oil to produce light olefins and aromatics

By using nano-ZSM-5 zeolite and ultrastable Y-type zeolite in fluidized catalytic cracking units to treat the hydrocarbon feed, the problems of limited catalyst selectivity and yield in the prior art are solved, achieving high Selective and high yields of light olefin production.

CN119497745APending Publication Date: 2025-02-21SAUDI ARABIAN OIL CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051467.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-06-23
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, when cracking hydrocarbon feed, the selectivity and yield of the catalyst are limited, making it difficult to effectively produce light olefins with high selectivity and high yield.

Method used

The hydrocarbon feed is treated with an FCC catalyst composition containing nano-ZSM-5 zeolite and superstable Y-type zeolite in the fluidized catalytic cracking unit, and the selectivity and yield of the cracking reaction are improved by adjusting the composition and process conditions of the catalyst.

Benefits of technology

The selectivity and light olefin yield of unconventional hydrocarbon feeds during fluid catalytic cracking are improved, coke formation and pore diffusion are reduced, catalyst deactivation rate is reduced, and production economy is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497745A_ABST
    Figure CN119497745A_ABST
Patent Text Reader

Abstract

A process for converting crude oil to light olefins, aromatics, or both, the process comprising contacting the crude oil with an FCC catalyst composition in a fluid catalytic cracking system at a temperature greater than or equal to 580 DEG C, the weight ratio of FCC catalyst to crude oil being from 2: 1 to 10: 1, and the residence time being from 0.1 to 60 seconds. The contacting causes at least a portion of the hydrocarbons in the crude oil to undergo a cracking reaction to produce a cracked effluent comprising at least olefins. FCC catalyst compositions for the production of olefins and aromatics from crude oil include an ultra-stable Y-type zeolite impregnated with lanthanum, a nano-ZSM-5 zeolite impregnated with phosphorus, wherein the nano-ZSM-5 zeolite has an average particle size of 0.01 [mu] m to 0.2 [mu] m, an alumina binder, colloidal silica, and a matrix material comprising kaolin.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. application serial number: 17 / 858,242 filed on July 6, 2022, the entire disclosure of which is incorporated herein by reference. Background Art Technical Field

[0003] The present disclosure relates to methods and catalyst formulations for processing petroleum-based materials, and in particular to methods and catalytic compositions for cracking hydrocarbon feeds to produce olefins and aromatic compounds. Technical Background

[0005] The growing global demand for light olefins remains a major challenge for many integrated refineries. In particular, the production of some valuable light olefins, such as ethylene and propylene, has attracted increasing attention, as pure olefin streams are considered to be the building blocks for polymer synthesis. The production of light olefins depends on several process variables, such as feed type, operating conditions, and catalyst type. Although there are options available for producing higher yields of propylene and light olefins, research activities in this field are still intensively ongoing. For example, light olefins are typically produced by thermal cracking (or steam pyrolysis) of petroleum gas and fractions, such as naphtha, kerosene, or gas oil. Light olefins can also be produced by fluid catalytic cracking processes. Typical hydrocarbon feeds for fluid catalytic cracking processes range from hydrocracking bottoms to heavy feed fractions, such as vacuum gas oil and atmospheric residue; however, these hydrocarbon feeds are limited, at least in part due to limitations of traditional catalysts used in fluid catalytic cracking processes. Summary of the invention

[0006] Therefore, compared with the conventional method of cracking hydrocarbon feed, the method of cracking hydrocarbon raw material is continuously needed to produce olefins with higher selectivity and light olefin yield by hydrocarbon feed.The method of the present disclosure is included in the treatment of hydrocarbon feed with FCC catalyst composition in fluid catalytic cracking unit.Especially, the method of the present disclosure includes contacting hydrocarbon feed with FCC catalyst composition comprising nano-ZSM-5 zeolite and ultrastable Y-type zeolite, wherein the average particle size of nano-ZSM-5 zeolite is 0.01 micron (um) to 0.2 micron.Comprising these different zeolite components can improve the selectivity and light olefin yield in the whole range of some unconventional hydrocarbon feeds (such as crude oil) in fluid catalytic cracking process.In addition, the reduction of nano-ZSM-5 zeolite size can reduce coke formation and pore diffusion on FCC catalyst composition.FCC catalyst composition can also show the deactivation rate of reduction, which can improve the economy of light olefin production, as well as other features.

[0007] According to at least one aspect of the present disclosure, a method for converting crude oil into light olefins, aromatic compounds, or both includes contacting the crude oil with a fluid catalytic cracking (FCC) catalyst composition in an FCC system at a temperature greater than or equal to 580° C., the weight ratio of the FCC catalyst to the crude oil being 2:1 to 10:1, and the residence time being 0.1 to 60 seconds, wherein the FCC catalyst may comprise an ultrastable Y-type zeolite (USY zeolite) impregnated with lanthanum, a nano-ZSM-5 zeolite impregnated with phosphorus (wherein the nano-ZSM-5 zeolite may have an average particle size of 0.01 μm to 0.2 μm), an alumina binder, colloidal silica, and a matrix material comprising kaolin, and the contacting may cause at least a portion of the hydrocarbons in the crude oil to undergo a cracking reaction to produce a cracking effluent comprising at least olefins.

[0008] According to at least one aspect of the present disclosure, an FCC catalyst composition for producing olefins and aromatic compounds from crude oil may include an ultrastable Y-type zeolite (USY zeolite) impregnated with lanthanum, a nano-ZSM-5 zeolite impregnated with phosphorus (wherein the nano-ZSM-5 zeolite has an average particle size of 0.01 μm to 0.2 μm), an alumina binder, colloidal silica, and a matrix material comprising kaolin.

[0009] Additional features and advantages of various aspects of the disclosure will be set forth in the detailed description that follows and, in part, will be apparent to those skilled in the art from the detailed description or by practicing various aspects of the disclosure.

[0010] BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The following detailed description of the present disclosure may be better understood when read in conjunction with the following drawings, in which:

[0012] Figure 1 A generalized flow diagram of a system for converting a hydrocarbon feed to produce olefins according to one or more aspects of the present disclosure is schematically depicted.

[0013] When describing Figure 1 While the simplified schematic diagram does not include the many valves, temperature sensors, electronic controllers, etc. that are available and well known to those of ordinary skill in the art. In addition, those typically included in Figure 1 Accompanying components in the illustrated system, such as air supplies, heat exchangers, surge tanks, etc., are also not included. However, one of ordinary skill in the art would understand that such components are within the scope of the present disclosure.

[0014] also, Figure 1The arrows in the simplified schematics of refer to process flows. However, the arrows may equally refer to transmission lines, which may transmit process flows between two or more system components. Arrows connected to one or more system components refer to inlets or outlets in a given system component, and arrows connected to only one system component represent system outlet flows leaving the depicted system or system inlet flows entering the depicted system. The arrow direction generally corresponds to the primary direction of motion of the process flow or flows contained within the physical transmission line depicted by the arrow.

[0015] Figure 1 Arrows in simplified schematic diagrams of can also refer to process steps that transfer a process stream from one system component to another system component. For example, an arrow pointing from a first system component to a second system component can represent "transferring" a process stream from the first system component to the second system component, which can include the process stream "leaving" or being "removed" from the first system component and "introducing" a process stream into the second system component.

[0016] Reference will now be made in greater detail to the various aspects, some of which are illustrated in the accompanying drawings. DETAILED DESCRIPTION

[0017] The present disclosure relates to a catalyst composition and method for upgrading crude oil and other heavy hydrocarbon streams by fluid catalytic cracking to produce more valuable chemical products and intermediates (such as, but not limited to, light olefins, aromatic compounds, and combinations thereof). The FCC catalyst composition of the present disclosure may include an ultrastable Y-type zeolite (USY zeolite) impregnated with lanthanum, a nano-ZSM-5 zeolite impregnated with phosphorus, an alumina binder, colloidal silica, and a matrix material comprising kaolin. The average particle size of the nano-ZSM-5 zeolite is 0.01 microns (μm) to 0.2 μm. The method of the present disclosure includes contacting crude oil or other heavy hydrocarbon streams with an FCC catalyst composition in a fluid catalytic cracking (FCC) system at a temperature greater than or equal to 580°C, the weight ratio of the FCC catalyst to the crude oil being 2:1 to 10:1, and the residence time being 0.1 seconds to 60 seconds.

[0018] The FCC catalyst composition and method of the present disclosure can ensure direct fluid catalytic cracking of heavy hydrocarbon feeds including crude oil (such as Arabian light crude oil). The FCC catalyst composition of the present disclosure can ensure effective cracking of crude oil feed streams while exhibiting a reduced rate of FCC catalyst composition deactivation due to contaminants and coke formation, as well as other features.

[0019] As used in this disclosure, the term "cracking" refers to a chemical reaction in which a molecule having a carbon-carbon bond is broken into more than one molecule by breaking one or more carbon-carbon bonds; in which a compound including a cyclic portion (such as an aromatic compound) is converted into a compound that does not include a cyclic portion; or in which a molecule having a carbon-carbon double bond is reduced to a carbon-carbon single bond. As used in this disclosure, the term "catalytic cracking" refers to cracking performed in the presence of a catalyst. Some catalysts can have multiple forms of catalytic activity, and the catalyst is called upon by a specific function without rendering the catalyst incapable of catalytic activity for other functions.

[0020] As used in this disclosure, the term "catalyst" refers to any substance that increases the rate of a particular chemical reaction, such as a cracking reaction.

[0021] As used in this disclosure, the term "spent catalyst" refers to a catalyst that has been in contact with reactants under reaction conditions but has not been regenerated in a regenerator. "Spent catalyst" may have coke deposited on the catalyst and may include partially coked catalyst and fully coked catalyst. The amount of coke deposited on "spent catalyst" may be greater than the amount of coke remaining on the regenerated catalyst after regeneration. "Spent catalyst" may also include a catalyst that has a reduced temperature due to contact with the reactants compared to the catalyst before contact with the reactants.

[0022] As used in this disclosure, the term "regenerated catalyst" refers to a catalyst that is contacted with reactants under reaction conditions and then regenerated in a regenerator to heat the catalyst to a higher temperature, oxidize and remove at least a portion of the coke from the catalyst to restore at least a portion of the catalytic activity of the catalyst, or both. A "regenerated catalyst" may have less coke, a higher temperature, or both than a used catalyst, and may have greater catalytic activity than a used catalyst. A "regenerated catalyst" may have more coke and lower catalytic activity than a fresh catalyst that has not passed through a cracking reaction zone and a regenerator.

[0023] As used in this disclosure, the term "deactivated catalyst" refers to a catalyst that has lost its functionality and is distinguished from a spent catalyst in that a deactivated catalyst generally cannot be regenerated in a regenerator during steady-state operation of a regeneration system. The deactivated catalyst may be deactivated by contaminants and / or metals in the hydrocarbon feed or steam feed that are deposited on the catalyst surface.

[0024] As used in this disclosure, the term "crude oil" refers to a mixture of petroleum liquids and gases (including impurities, such as sulfur-containing compounds, nitrogen-containing compounds, and metallic compounds) that is extracted directly from an underground formation or received from a desalting unit without separating any fractions, such as naphtha, by distillation.

[0025] The term "naphtha" as used in the present disclosure refers to an intermediate mixture of hydrocarbonaceous materials derived from crude oil refining, and has an atmospheric boiling point of 36 degrees Celsius (° C.) to 220° C. Naphtha may include light naphtha, intermediate naphtha, and heavy naphtha, wherein light naphtha includes hydrocarbonaceous materials having an atmospheric boiling point of 36° C. to 80° C., intermediate naphtha includes hydrocarbonaceous materials having an atmospheric boiling point of 80° C. to 140° C., and heavy naphtha includes hydrocarbonaceous materials having an atmospheric boiling point of 140° C. to 200° C. Naphtha may include paraffinic hydrocarbons, cycloparaffinic hydrocarbons, and aromatic hydrocarbons having 4 to 11 carbon atoms.

[0026] As used in this disclosure, the term "directly" refers to passing a material (e.g., an effluent) from a first component of the FCC system 100 to a second component of the FCC system 100, without passing the material through any intermediate component or system that is operable to change the composition of the material. Similarly, the term "directly" also refers to introducing a material (e.g., a feed) into a component of the FCC system 100, without passing the material through any preliminary component that is operable to change the composition of the material. Intermediate components or systems or preliminary components or systems that are operable to change the composition of a material may include reactors and separators, but are generally not intended to include heat exchangers, valves, pumps, sensors, or other auxiliary components required for the operation of a chemical process. In addition, combining two streams together upstream of the second component, rather than passing each stream separately to the second component, is also not considered an intermediate component or preliminary component that is operable to change the composition of the material.

[0027] As used in this disclosure, the terms "downstream" and "upstream" refer to the positioning of components or systems of the FCC system 100 relative to the direction of flow of material through the FCC system 100. For example, if material flowing through the FCC system 100 encounters a first component before encountering a second component, the second component may be considered "downstream" of the first component. Likewise, if material flowing through the FCC system 100 encounters the first component before encountering the second component, the first component may be considered "upstream" of the second component.

[0028] As used in this disclosure, the term "effluent" refers to a stream that flows out of a reactor, reaction zone, or separator after a particular reaction or separation. Typically, the effluent has a different composition than the stream that enters the reactor, reaction zone, or separator. It should be understood that when an effluent passes through another component or system, only a portion of the effluent can pass through. For example, a slip stream may carry away some of the effluent, meaning that only a portion of the effluent can enter a downstream component or system. The terms "reaction effluent" and "reactor effluent" particularly refer to a stream that flows out of a reactor or reaction zone.

[0029] As used in this disclosure, the term "high severity conditions" refers to operating conditions of a fluid catalytic cracking system (such as FCC system 100), including a temperature greater than or equal to 580°C, or from 580°C to 750°C, a catalyst to oil ratio greater than or equal to 1:1, or from 1:1 to 60:1, and a residence time less than or equal to 60 seconds, or from 0.1 seconds to 60 seconds, each of which may be more severe than typical operating conditions of a fluid catalytic cracking system.

[0030] As used in this disclosure, the term "catalyst to oil ratio" or "CTO weight ratio" refers to the weight ratio of catalyst (such as the FCC catalyst composition of the FCC system 100) to a process stream comprising hydrocarbons (such as the hydrocarbon feed 102 of the FCC system 100).

[0031] The term "residence time" refers to the amount of time that reactants (eg, hydrocarbons in hydrocarbon feed 102 of FCC system 100) are in contact with a catalyst under reaction conditions (eg, reaction temperature).

[0032] As used in this disclosure, the term "particle size" refers to the maximum length from one side of a particle to the other side measured along the longest distance of the particle. "Average particle size" is the average of the particle sizes occupied by a sample of particles. For spherical particles, the average particle size is equal to the average particle diameter of the spherical particles determined by electron microscopy.

[0033] As used in this disclosure, the term "reactor" refers to any vessel, container, pipe, etc., in which a chemical reaction (such as catalytic cracking) occurs between one or more reactants, optionally in the presence of one or more catalysts. A reactor may include one or more "reaction zones" disposed within the reactor. The term "reaction zone" refers to an area in a reactor where a particular reaction occurs.

[0034] As used in the present disclosure, the terms "separation unit" and "separator" refer to any separation device that at least partially separates one or more chemical components in a mixture from each other. For example, a separation system selectively separates different chemical components from each other to form one or more chemical fractions. Examples of separation systems include, but are not limited to, distillation columns, fractionators, flash tanks, knock-out drums, knock-out pots, centrifuges, filtration devices, traps, washers, expansion devices, membranes, solvent extraction devices, high-pressure separators, low-pressure separators, or combinations thereof. The separation methods described in the present disclosure may not completely separate all of one chemical component from all other chemical components. Instead, the separation methods described in the present disclosure "at least partially" separate different chemical components from each other, even if not explicitly stated, and the separation may include only partial separation.

[0035] It should be further understood that a stream can be named according to a component of the stream, and the component used to name the stream can be the major component of the stream (e.g., comprising a stream content of from 50 wt%, 70 wt%, 90 wt%, 95 wt%, 99 wt%, 99.5 wt%, or 99.9 wt% to 100 wt%. It should also be understood that when a stream comprising the component is disclosed as being transferred from the system component to another system component, the component of the stream is disclosed as being transferred from one system component to another system component. For example, a disclosed "heavy oil stream" being transferred to a first system component or from a first system component to a second system component should be understood to be equivalently disclosed as "heavy oil" being transferred to the first system component or from a first system component to a second system component.

[0036] The composition of the feed stream and the process variables of the FCC system play an important role in the reaction yield and heat balance within the system. Conventional FCC systems and processes may require expensive refining to produce suitable feed streams. This additional expensive refining may include separating and processing one or more hydrocarbon feed fractions before the refined conventional feed is introduced into the FCC system. These additional processing steps are energy intensive and reduce the feasible feed amount of existing hydrocarbon sources. Previous systems and methods that have been developed directly convert crude oil into more valuable chemical products and intermediates through catalytic cracking in an attempt to overcome these limitations, such as by reducing or eliminating the processing steps required to produce suitable hydrocarbon feeds before being introduced into the FCC system. However, pollutants, metals, or both present in heavy hydrocarbon feeds (such as crude oil) can deactivate the catalyst, resulting in reduced yields and increased production costs.

[0037] Therefore, various aspects of the present disclosure relate to FCC catalyst compositions and methods for directly converting crude oil into higher value chemical products and intermediates, such as but not limited to olefins and aromatic compounds, while resisting catalyst deactivation by using an FCC system of the FCC catalyst composition and reaction conditions that result in effective cracking of crude oil. The FCC catalyst composition of the present disclosure includes nano-ZSM-5 zeolite, ultrastable Y-type zeolite, an alumina binder, a matrix material comprising kaolin, and colloidal silica. The method of the present disclosure includes contacting a crude oil feed stream with an FCC catalyst composition in a fluidized catalytic cracking (FCC) system under high severity conditions sufficient to convert at least a portion of the crude oil feed stream into light olefins, aromatic compounds, or both. The FCC catalyst composition and reaction conditions of the method of the present disclosure enable crude oil to be effectively directly converted into light olefins, aromatic compounds, or both, while resisting catalyst deactivation, as well as other features.

[0038] Reference now Figure 1, schematically depicts an FCC system 100 of the present disclosure for processing a hydrocarbon feed 102 to produce olefins. The FCC system 100 may include a fluidized catalytic cracking unit 120 and a regenerator 160. The fluidized catalytic cracking unit 120 contacts the hydrocarbon feed 102 with an FCC catalyst composition 124 to produce a spent FCC catalyst and a cracking effluent. The regenerator 160 may process the spent FCC catalyst to produce a regenerated FCC catalyst, which may be recycled back to the fluidized catalytic cracking unit 120.

[0039] The hydrocarbon feed 102 may include one or more heavy oils, such as, but not limited to, crude oil, topped crude oil, vacuum residue, tar sands, asphalt, atmospheric residue, vacuum gas oil, other heavy oil streams, or combinations thereof. It should be understood that, as used in the present disclosure, "heavy oil" refers to: a raw hydrocarbon (such as crude oil) that has not been previously treated by distillation, a hydrocarbon that has been treated to a certain extent (such as desalting) before being introduced into the FCC system 100 as a hydrocarbon feed 102, or a combination of the two. The hydrocarbon feed 102 may have an end boiling point (EBP) greater than or equal to 720°C. The hydrocarbon feed 102 may have an initial boiling point greater than 30°C. The hydrocarbon feed 102 may have an initial boiling point of 30°C to 50°C. The hydrocarbon feed 102 may have a nitrogen concentration less than or equal to 900 parts per million by weight (ppmw).

[0040] In embodiments, hydrocarbon feed 102 is crude oil. Crude oil can have an American Petroleum Institute (API) gravity of 15 to 50 degrees, such as 20 to 50 degrees, 20 to 40 degrees, 20 to 35 degrees, 25 to 50 degrees, 25 to 40 degrees, 25 to 35 degrees, 30 to 50 degrees, or 30 to 40 degrees. For example, hydrocarbon feed 102 can be Arab light (AL) crude oil. Crude oil can have a density greater than 0.8 grams per milliliter (g / mL), greater than 0.82 g / mL, greater than 0.84 g / mL, or even greater than 0.85 g / mL measured at 15 ° C. In embodiments, crude oil can have a density less than or equal to 1.0 g / mL, less than or equal to 0.95 g / mL, less than or equal to 0.90 g / mL, or even less than or equal to 0.88 g / mL measured at 15 ° C. In embodiments, hydrocarbon feed 102 is Arab light crude oil. Table 1 provides properties of exemplary grades of Arabian Light crude oil.

[0041] Table 1

[0042]

[0043]

[0044] When hydrocarbon feed 102 comprises crude oil, is composed of crude oil or is substantially composed of crude oil, crude oil can be whole crude oil or crude oil that has undergone at least some treatment, such as desalting, solid separation, washing or a combination of these, but has not been distilled. For example, hydrocarbon feed 102 can be a desalted crude oil that has been treated with desalting. In embodiments, hydrocarbon feed 102 can include crude oil that has not undergone other operations of pretreatment, separation (such as distillation) or changing the hydrocarbon composition of crude oil before crude oil is introduced into FCC system 100. As used herein, the "hydrocarbon composition" of crude oil refers to the composition of the hydrocarbon components of crude oil, and does not include entrained non-hydrocarbon solids, salts, water or other non-hydrocarbon components.

[0045] In an embodiment, the hydrocarbon feed 102 may be a crude oil having an initial boiling point temperature greater than or equal to 30°C (e.g., 30°C to 50°C or 30°C to 40°C) as determined by standard test method ASTM D7169. In an embodiment, the hydrocarbon feed 102 may be a crude oil having a final boiling point temperature greater than 720°C as determined by standard test method ASTM D7169. In an embodiment, the hydrocarbon feed 102 may be a crude oil having a boiling point temperature greater than 300°C, e.g., 300°C to 400°C, 300°C to 380°C, 300°C to 375°C, 350°C to 400°C, 350°C to 380°C, 350°C to 375°C, 360°C to 400°C, 360°C to 380°C, or even 360°C to 375°C as determined by standard test method ASTM D7169.

[0046] In embodiments, the hydrocarbon feed 102 may have a concentration of less than 50 wt % paraffin compounds per unit weight of the hydrocarbon feed, e.g., less than or equal to 40 wt %, less than or equal to 35 wt %, less than or equal to 30 wt %, less than or equal to 25 wt %, or even less than or equal to 20 wt %, as determined according to ASTM 5443. In embodiments, the hydrocarbon feed 102 may have a concentration of from 5 wt % to less than 50 wt %, from 5 wt % to 40 wt %, from 5 wt % to 35 wt %, from 5 wt % to 30 wt %, from 5 wt % to 25 wt %, from 5 wt % to 20 wt %, from 10 wt % to less than 50 wt %, from 10 wt % to 40 wt %, from 10 wt % to 35 wt %, from 10 wt % to 30 wt %, from 10 wt % to 25 wt %, or even from 10 wt % to 20 wt % paraffin compounds per unit weight of the hydrocarbon feed 102.

[0047] In embodiments, the hydrocarbon feed 102 may have a concentration of aromatic compounds of greater than or equal to 20 wt%, greater than or equal to 30 wt%, greater than or equal to 40 wt%, or even greater than or equal to 50 wt%, per unit weight of the hydrocarbon feed 102, as determined in accordance with ASTM 5443. In embodiments, the hydrocarbon feed 102 may have a concentration of aromatic compounds of from 20 wt% to 90 wt%, from 20 wt% to 80 wt%, from 20 wt% to 70 wt%, from 30 wt% to 90 wt%, from 30 wt% to 80 wt%, from 30 wt% to 70 wt%, from 40 wt% to 90 wt%, from 40 wt% to 80 wt%, from 40 wt% to 70 wt%, from 50 wt% to 90 wt%, from 50 wt% to 80 wt%, or even from 50 wt% to 70 wt%, per unit weight of the hydrocarbon feed 102.

[0048] In embodiments, hydrocarbon feed 102 may have a concentration of cycloalkanes of greater than or equal to 25 wt %, or even greater than or equal to 27 wt %, per unit weight of hydrocarbon feed 102, as determined in accordance with ASTM 5443. In embodiments, hydrocarbon feed 102 may have a concentration of cycloalkanes of from 25 wt % to 60 wt %, from 25 wt % to 50 wt %, from 25 wt % to 40 wt %, from 25 wt % to 35 wt %, from 27 wt % to 60 wt %, from 27 wt % to 50 wt %, from 27 wt % to 40 wt %, or even from 27 wt % to 35 wt %, per unit weight of hydrocarbon feed 102.

[0049] In an embodiment, hydrocarbon feed 102 may be a topped crude oil. As used in this disclosure, the term "topped crude oil" refers to a crude oil from which lower boiling point components have been removed by distillation, such as components having a boiling point temperature below 180° C. or even below 160° C. In an embodiment, hydrocarbon feed 102 comprises, consists of, or consists essentially of a topped crude oil having greater than or equal to 95%, greater than or equal to 98%, or even greater than or equal to 99% of the components having a boiling point temperature greater than or equal to 160° C. or greater than or equal to 180° C., depending on the cut point temperature of the topping unit.

[0050] Although the present disclosure may specify the hydrocarbon feed 102 as crude oil or topped crude oil, it should be understood that the FCC system 100 of the present disclosure may also be applicable to the conversion of a wider variety of heavy hydrocarbon-containing feeds, such as, but not limited to, crude oil, vacuum residue, tar sands, asphalt, atmospheric residue, vacuum gas oil, demetallized oil, naphtha stream, or combinations thereof. The hydrocarbon feed 102 may also include one or more non-hydrocarbon components, such as heavy metals, sulfur compounds, nitrogen compounds, inorganic components, or combinations thereof.

[0051] In an embodiment, one or more supplemental feeds (not shown) may be mixed with the hydrocarbon feed 102 prior to introducing the hydrocarbon feed 102 into the fluid catalytic cracking unit 120, or one or more supplemental feeds may be introduced separately to the fluid catalytic cracking unit 120 in addition to the hydrocarbon feed 102. In an embodiment, the hydrocarbon feed 102 may be a crude oil, such as Arabian light crude oil, and one or more supplemental streams (such as vacuum residue, atmospheric residue, vacuum gas oil, demetallized oil, naphtha stream, or a combination of these) may be mixed with the hydrocarbon feed 102 upstream of the fluid catalytic cracking unit 120, or introduced separately to the fluid catalytic cracking unit 120.

[0052] The method of the present disclosure includes delivering a hydrocarbon feed 102 to an FCC system 100 comprising an FCC catalyst composition 124. The FCC catalyst composition 124 of the present disclosure includes a nano-ZSM-5 zeolite and a Y-type zeolite, wherein the nano-ZSM-5 has an average particle size of 0.01 μm to 0.2 μm. The FCC catalyst composition may also include an alumina binder, a matrix material comprising kaolin, and colloidal silica.

[0053] The nano-ZSM-5 zeolite in the FCC catalyst composition 124 can be operated to crack at least a portion of the hydrocarbon feed to produce one or more light olefins, such as ethylene and propylene. Without being bound by any particular theory, it is believed that the nano-ZSM-5 zeolite may be more inclined to crack relatively light hydrocarbons, such as those present in the hydrocarbon feed 102 and those produced by the catalytic cracking of heavier hydrocarbons by Y-type zeolite. Therefore, when compared with the FCC catalyst without nano-ZSM-5 zeolite, the yield of products such as light olefins can be improved by including nano-ZSM-5 zeolite. In addition, when compared with the FCC catalyst composition including the ZSM-5 zeolite with an average particle size greater than 0.2 μm, the catalytic cracking catalyst composition 124 including nano-ZSM-5 zeolite can reduce the formation of coke during the steady-state operation of the catalytic cracking system 100. As used in the present disclosure, "ZSM-5" refers to a zeolite having an MFI framework type and composed of silica and alumina according to the IUPAC zeolite nomenclature. ZSM-5 refers to "Zeolite Socony Mobil-5", a pentasil family zeolite that can be expressed in terms of chemical formula Na n Al n Si 96–n O 192·16H₂O, where 0 < n < 27. The molar ratio of silica to alumina in ZSM-5 can be at least 5, at least 10, at least 25, at least 30, or even at least 50. In an embodiment, the molar ratio of silica to alumina in ZSM-5 can be from 5 to 50, from 5 to 40, from 5 to 35, from 10 to 50, from 10 to 40, from 10 to 35, from 20 to 50, from 20 to 40, from 20 to 35, from 30 to 50, or from 30 to 40. As used in this disclosure, "nano-ZSM-5" refers to ZSM-5 zeolite having an average particle size of 0.01 μm to 0.2 μm as determined by electron microscopy.

[0054] In an embodiment, the nano-ZSM-5 zeolite can have from 200 square meters per gram (m 2 / g) to 800 m 2 / g of average surface area. In an embodiment, the average surface area can be from 200 m 2 / g to 400 m 2 / g, from 200 m 2 / g to 600 m 2 / g, from 200 m 2 / g to 800 m 2 / g, from 300 m 2 / g to 400 m 2 / g, from 300 m 2 / g to 600 m 2 / g, from 300 m 2 / g to 800 m 2 / g, from 400 m 2 / g to 600 m 2 / g, or from 400 m 2 / g to 800 m 2 / g. In an embodiment, the nano-ZSM-5 zeolite can have an average total pore volume per unit weight of the nano-ZSM-5 zeolite from 0.010 milliliters per gram (mL / g) to 0.500 mL / g, such as from 0.050 mL / g to 0.500 mL / g, from 0.010 mL / g to 0.300 mL / g, or from 0.050 mL / g to 0.300 mL / g.

[0055] In an embodiment, the nano-ZSM-5 zeolite may have an average particle size of 0.01 μm to 0.2 μm as determined by electron microscopy. In an embodiment, the average particle size of the nano-ZSM-5 zeolite may be 0.01 μm to 0.15 μm, 0.01 μm to 0.125 μm, 0.01 μm to 0.1 μm, 0.01 μm to 0.09 μm, 0.05 μm to 0.15 μm, 0.05 μm to 0.125 μm, 0.05 μm to 0.1 μm, 0.05 μm to 0.09 μm, or 0.08 μm to 0.09 μm. In embodiments, the nano-ZSM-5 zeolite may be roughly spherical and may have an average particle size of 0.01 μm to 0.15 μm, 0.01 μm to 0.125 μm, 0.01 μm to 0.1 μm, 0.01 μm to 0.09 μm, 0.05 μm to 0.15 μm, 0.05 μm to 0.125 μm, 0.05 μm to 0.1 μm, 0.05 μm to 0.09 μm, or 0.08 μm to 0.09 μm, as determined by electron microscopy. Without intending to be bound by any particular theory, it is believed that the ZSM-5 zeolite having an average particle size or an average particle size greater than 0.2 μm may have a crystal size more similar to the molecular diameter of light hydrocarbons when compared to the nano-ZSM-5 zeolite having an average particle size less than or equal to 0.2 μm. It is further believed that when the crystal size of the ZSM-5 zeolite is similar to the molecular diameter of the light hydrocarbons produced by the catalytic reaction, the diffusion of the reactant and product molecules within the micropores of the ZSM-5 zeolite can be the rate-limiting step of the catalytic reaction, which can increase the coke formation on the ZSM-5 zeolite. Therefore, it is believed that the FCC catalyst composition 124 including a nano-ZSM-5 zeolite having an average particle size of 0.01 μm to 0.20 μm can show reduced coke formation and reduced deactivation when compared to an FCC catalyst composition including a ZSM-5 zeolite having an average particle size greater than 0.2 μm.

[0056] In an embodiment, one or more zeolite components of the FCC catalyst composition 124 may include one or more phosphorus-containing compounds, such as phosphorus pentoxide (P2O5). Without being bound by any particular theory, it is believed that the phosphorus-containing compound can stabilize the structure of the zeolite framework structure by preventing segregation of the framework alumina, which can improve the hydrothermal stability of the zeolite component. This can reduce the dealumination of the zeolite component that occurs during the steaming process - which can lead to a decrease in the acidity and catalytic activity of the zeolite component. In an embodiment, based on the total weight of each zeolite component, the one or more zeolite components of the FCC catalyst composition 124 may include one or more phosphorus-containing compounds in an amount of 1 wt % to 20 wt %. In an embodiment, the phosphorus-containing compound can be impregnated on the nano-ZSM-5 zeolite so as to impregnate the nano-ZSM-5 zeolite with 1 wt % to 20 wt % of the phosphorus-containing compound based on the total weight of the nano-ZSM-5 zeolite. In an embodiment, the nano-ZSM-5 zeolite can be impregnated with 1 wt % to 20 wt % of phosphorus pentoxide based on the total weight of the nano-ZSM-5 zeolite. In embodiments, the nano-ZSM-5 zeolite may comprise 1 wt % to 15 wt %, 1 wt % to 10 wt %, 1 wt % to 5 wt %, 5 wt % to 20 wt %, 5 wt % to 15 wt %, 5 wt % to 10 wt %, 10 wt % to 20 wt %, 10 wt % to 15 wt %, 15 wt % to 20 wt %, 6 wt % to 9 wt %, or 7 wt % to 8 wt % of phosphorus pentoxide, based on the total weight of the nano-ZSM-5 zeolite. In embodiments, the nano-ZSM-5 zeolite may comprise about 7.5 wt % of phosphorus pentoxide, based on the total weight of the nano-ZSM-5 zeolite.

[0057] In embodiments, the FCC catalyst composition 124 may include up to 40 wt% nano-ZSM-5 zeolite, based on the total weight of the FCC catalyst composition 124. In embodiments, the FCC catalyst composition 124 may include up to 30 wt%, up to 25 wt%, or up to 20 wt% nano-ZSM-5 zeolite, based on the total weight of the FCC catalyst composition 124. In embodiments, the FCC catalyst composition 124 may include 1 wt % to 40 wt %, 1 wt % to 30 wt %, 1 wt % to 25 wt %, 1 wt % to 20 wt %, 5 wt % to 40 wt %, 5 wt % to 30 wt %, 5 wt % to 25 wt %, 5 wt % to 20 wt %, 10 wt % to 40 wt %, 10 wt % to 30 wt %, 10 wt % to 25 wt %, 10 wt % to 20 wt %, 15 wt % to 40 wt %, 15 wt % to 30 wt %, 15 wt % to 25 wt %, or 15 wt % to 20 wt % nano-ZSM-5 zeolite, based on the total weight of the FCC catalyst composition 124.

[0058] The Y-type zeolite of the FCC catalyst composition 124 can be operated to produce one or more olefins from the hydrocarbons in the hydrocarbon feed 102. In an embodiment, the Y-type zeolite can include an ultrastable Y-type (USY) zeolite. USY zeolite can be produced by the dealumination of one or more Y-type zeolites. As used in the present disclosure, the term "Y-type zeolite" refers to a zeolite having a FAU framework type and consisting of silica and alumina according to the IUPAC zeolite nomenclature. Without being bound by any particular theory, it is believed that the dealumination of the Y-type zeolite can lead to a reduction in the number of acid sites of the USY zeolite. When compared to a Y-type zeolite that is not dealuminated, the reduction in the number of acid sites can lead to a reduction in the rate of secondary reactions in the FCC system 100, such as the dehydrogenation or hydrogenation of the olefins produced by the FCC system 100. Therefore, when compared to the Y-type zeolite, the USY zeolite can produce a higher olefin yield.

[0059] The molar ratio of silica to alumina in the USY zeolite may be greater than or equal to 5, greater than or equal to 10, greater than or equal to 25, or even greater than or equal to 50. In embodiments, the molar ratio of silica to alumina in the USY zeolite may be from 5 to 50, from 5 to 25, from 5 to 10, from 10 to 50, from 10 to 25, or from 25 to 50. In embodiments, the molar ratio of silica to alumina in the USY zeolite may be about 30. In embodiments, the USY zeolite may also include one or more transition metals substituted into the framework of the zeolite, such as zirconium, titanium, or hafnium. The USY zeolite may have 200 m 2 / g to 900m 2 In embodiments, the USY zeolite may have an average surface area of ​​200 m 2 / g to 800m 2 / g、300m 2 / g to 900m 2 / g、300m 2 / g to 800m 2 / g、500m 2 / g to 900m 2 / g or 500m 2 / g to 800m 2 The USY zeolite may have an average total pore volume per unit weight of the USY zeolite of 0.050 mL / g to 0.600 mL / g, for example, 0.050 mL / g to 0.500 mL / g.

[0060] In an embodiment, the one or more zeolite components of the FCC catalyst composition 124 may include one or more rare earth metals or rare earth metal oxides, wherein the rare earth metal may be one or more of lanthanum, cerium, dysprosium, europium, gadolinium, holmium, lutetium, neodymium, praseodymium, promethium, samarium, scandium, terbium, thulium, ytterbium, yttrium, or a combination of these. Without being bound by any particular theory, it is believed that the rare earth metal or rare earth metal oxide can improve the stability of the zeolite component unit cell, increase the catalytic activity of the zeolite component, or both. In addition, it is believed that the rare earth metal or rare earth metal oxide can act as a vanadium collector, which acts to isolate vanadium in the feed and prevent the harmful effects that vanadium may have on the zeolite component of the catalyst. In an embodiment, the one or more zeolite components of the FCC catalyst composition 124 may include one or more rare earth metals in an amount of 1% to 5% by weight based on the total weight of each zeolite component. In an embodiment, the one or more zeolite components of the FCC catalyst composition 124 may be impregnated with lanthanum or lanthanum oxide. In embodiments, one or more zeolite components of the FCC catalyst composition 124 may include one or more lanthanum-containing compounds, such as, but not limited to, lanthanum oxide, in an amount from 1 wt % to 5 wt %, 1 wt % to 4 wt %, 1 wt % to 3 wt %, 1 wt % to 2 wt %, 2 wt % to 5 wt %, 2 wt % to 4 wt %, 2 wt % to 3 wt %, 3 wt % to 5 wt %, 3 wt % to 4 wt %, or 4 wt % to 5 wt %, based on the total weight of each zeolite component.

[0061] In an embodiment, a rare earth or rare earth oxide may be impregnated on the USY zeolite of the FCC catalyst composition 124. In an embodiment, the FCC catalyst composition 124 may include a USY zeolite impregnated with lanthanum oxide (La2O3). In an embodiment, the USY zeolite may include 1 wt% to 5 wt%, 1 wt% to 4 wt%, 1 wt% to 3 wt%, 1 wt% to 2 wt%, 2 wt% to 5 wt%, 2 wt% to 4 wt%, 2 wt% to 3 wt%, 3 wt% to 5 wt%, 3 wt% to 4 wt%, or 4 wt% to 5 wt% of lanthanum oxide, based on the total weight of the USY zeolite. In an embodiment, the USY zeolite may include about 2.5 wt% of lanthanum oxide, based on the total weight of the USY zeolite.

[0062] In an embodiment, the FCC catalyst composition 124 may include up to 40 wt% USY zeolite, based on the total weight of the FCC catalyst composition 124. In an embodiment, the FCC catalyst composition 124 may include up to 30 wt% or up to 25 wt% USY zeolite, based on the total weight of the FCC catalyst composition 124. In an embodiment, the FCC catalyst composition 124 may include 1 wt% to 40 wt%, 1 wt% to 30 wt%, 1 wt% to 25 wt%, 5 wt% to 40 wt%, 5 wt% to 30 wt%, 5 wt% to 25 wt%, 10 wt% to 40 wt%, 10 wt% to 30 wt%, 10 wt% to 25 wt%, 15 wt% to 40 wt%, 15 wt% to 30 wt%, or 15 wt% to 25 wt% USY zeolite, based on the total weight of the FCC catalyst composition 124.

[0063] In an embodiment, the FCC catalyst composition 124 may include one or more binder materials, such as a compound containing alumina or a compound containing silica (including a compound containing alumina and silica). As used in the present disclosure, "binder material" refers to a material used to "bond" or otherwise retain the components of the FCC catalyst composition 124. Binder materials may be included to improve the wear resistance of the FCC catalyst composition 124. The binder may include alumina (such as amorphous alumina), silica-alumina (such as amorphous silica-alumina) or silica (such as amorphous silica). According to one or more embodiments, the binder material may include pseudoboehmite. As used in the present disclosure, "pseudoboehmite" refers to an aluminum-containing compound with a chemical composition of AlO (OH) composed of crystalline boehmite. Although boehmite also generally refers to aluminum hydroxide oxide, the water content of pseudoboehmite is generally more than that of boehmite. In an embodiment, the binder material may include amorphous silica. The amorphous silica may be in the form of colloidal silica. As used throughout this disclosure, the term "colloidal silica" refers to nanometer-sized particles of amorphous, non-porous silica. In embodiments, the FCC catalyst composition 124 may include an alumina binder, colloidal silica, or both.

[0064] In embodiments, the FCC catalyst composition 124 may include one or more binders in an amount of 5 wt % to 30 wt %, based on the total weight of the FCC catalyst composition 124. In embodiments, the FCC catalyst composition 124 may include one or more binders in an amount of 5 wt % to 25 wt %, 5 wt % to 20 wt %, 5 wt % to 15 wt %, 5 wt % to 10 wt %, 10 wt % to 25 wt %, 10 wt % to 20 wt %, 10 wt % to 15 wt %, 15 wt % to 30 wt %, 15 wt % to 25 wt %, 15 wt % to 20 wt %, 20 wt % to 30 wt %, 20 wt % to 25 wt %, or 25 wt % to 30 wt %, based on the total weight of the FCC catalyst composition 124.

[0065] In embodiments, the FCC catalyst composition 124 may include an alumina binder in an amount of 2 wt % to 20 wt %, based on the total weight of the FCC catalyst composition 124. In embodiments, the FCC catalyst composition 124 may include an alumina binder in an amount of 2 wt % to 15 wt %, 2 wt % to 10 wt %, 5 wt % to 20 wt %, 5 wt % to 15 wt %, 5 wt % to 10 wt %, or 7 wt % to 9 wt %, based on the total weight of the FCC catalyst composition 124. In embodiments, the FCC catalyst composition 124 may include about 8 wt % alumina binder, based on the total weight of the FCC catalyst composition 124.

[0066] In an embodiment, based on the total weight of the FCC catalyst composition 124, the FCC catalyst composition 124 may include colloidal silica in an amount of 0.5 wt % to 5 wt %. In an embodiment, based on the total weight of the FCC catalyst composition 124, the FCC catalyst composition 124 may include colloidal silica in an amount of 0.5 wt % to 4 wt %, 0.5 wt % to 3 wt %, 0.5 wt % to 2 wt %, 1 wt % to 4 wt %, 1 wt % to 3 wt %, 1 wt % to 2 wt %, 2 wt % to 4 wt %, or 2 wt % to 3 wt %. In an embodiment, based on the total weight of the FCC catalyst composition 124, the FCC catalyst composition may include about 2 wt % of colloidal silica. Without intending to be bound by any particular theory, it is believed that colloidal silica can be used as a binder and / or filler to provide additional physical strength and integrity to the FCC catalyst. In addition, it is believed that adding colloidal silica to the FCC catalyst can improve the wear resistance of the FCC catalyst and / or stabilize the catalytic activity of the FCC catalyst.

[0067] In an embodiment, the FCC catalyst composition 124 may include one or more matrix materials, which may include one or more clay materials, such as, but not limited to, kaolin. Without being bound by any particular theory, it is believed that the matrix material of the FCC catalyst composition 124 may have both physical and catalytic functions. The physical function may include providing particle integrity and wear resistance, serving as a heat transfer medium, and providing a porous structure to allow hydrocarbons to diffuse into or diffuse out of the catalyst microspheres. The matrix material may also affect the selectivity, product quality, and anti-toxicity of the catalyst. For those reactions directly involving relatively large molecules, the matrix material may tend to have its strongest impact on the overall catalytic performance.

[0068] In an embodiment, the matrix material may include kaolin. As used in the present disclosure, "kaolin" refers to a clay material having a relatively large amount (e.g., at least about 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, 90 wt%, or at least 95 wt%) of kaolinite, which may be represented by the chemical formula Al2Si2O5(OH)4. In an embodiment, the FCC catalyst composition 124 may include one or more matrix materials in an amount of 30 wt% to 60 wt%, based on the total weight of each FCC catalyst composition. In embodiments, the FCC catalyst composition 124 may include 30 wt% to 55 wt%, 30 wt% to 50 wt%, 30 wt% to 45 wt%, 30 wt% to 40 wt%, 30 wt% to 35 wt%, 35 wt% to 60 wt%, 35 wt% to 55 wt%, 35 wt% to 50 wt%, 35 wt% to 45 wt%, 35 wt% to 40 wt%, 40 wt% to 60 wt%, 40 wt% to 55 wt%, 40 wt% to 50 wt%, 40 wt% to 45 wt%, 45 wt% to 60 wt%, 45 wt% to 55 wt%, 45 wt% to 50 wt%, 50 wt% to 60 wt%, 50 wt% to 55 wt%, or 55% to 60% matrix material based on the total weight of the FCC catalyst composition 124.

[0069] In an embodiment, the FCC catalyst composition 124 may include a nano-ZSM-5 zeolite impregnated with phosphorus, a USY zeolite impregnated with lanthanum oxide, an alumina binder, a matrix material comprising kaolin, and colloidal silica. In an embodiment, the nano-ZSM-5 zeolite may be impregnated with 7.5 wt % of phosphorus pentoxide based on the total weight of the nano-ZSM-5 zeolite. In an embodiment, the USY zeolite may be impregnated with 2.5 wt % of lanthanum oxide based on the total weight of the USY zeolite.

[0070] In an embodiment, the FCC catalyst composition 124 may include: 20 wt% of nano-ZSM-5 zeolite, based on the total weight of the FCC catalyst composition 124, wherein the nano-ZSM-5 zeolite is impregnated with 7.5 wt% of P2O5, based on the total weight of the nano-ZSM-5 zeolite; 21 wt% of USY zeolite, based on the total weight of the FCC catalyst composition 124, wherein the USY zeolite is impregnated with 2.5 wt% of lanthanum oxide (La2O3), based on the total weight of the USY zeolite; 8 wt% of alumina binder, based on the total weight of the FCC catalyst composition 124; 49 wt% of kaolin, based on the total weight of the FCC catalyst composition 124; and 2 wt% of colloidal silica, based on the total weight of the FCC catalyst composition 124. In an embodiment, the FCC catalyst composition 124 may comprise a plurality of catalyst particles, wherein each of the plurality of catalyst particles comprises nano-ZSM-5 zeolite impregnated with phosphorus pentoxide, USY zeolite impregnated with lanthanum oxide, an alumina binder, kaolin, and colloidal silica.

[0071] The FCC catalyst composition 124 can be formed by a variety of methods. According to one embodiment, the matrix material can be mixed with a fluid such as water to form a slurry, and the zeolite can be mixed with a fluid such as water alone to form a slurry. The matrix material slurry and the zeolite slurry can be combined under stirring. In addition, another slurry can be formed by combining a binder material with a fluid such as water. The binder slurry can then be combined with a slurry containing zeolite and matrix material to form a final slurry. The final slurry can then be dried, for example by spraying, and then calcined to produce particles of the cracking catalyst.

[0072] In an embodiment, the FCC catalyst composition 124 can be in the form of shaped particles, such as microspheres. As used in the present disclosure, "particles" refer to particles with an average particle size of 0.1 microns to 100 microns. The size of a particle refers to the maximum length from one side of the particle to the other side measured along the longest distance of the particle. For example, the size of a spherical particle is equal to its diameter, or the maximum length of a rectangular prism-shaped particle is equal to the hypotenuse extending from the opposite angle. In an embodiment, each zeolite component of the FCC catalyst composition 124 can be included in each catalyst particle. However, in other embodiments, particles can be mixed, wherein the particles contain only a portion of the FCC catalyst composition 124. For example, a mixture of two types of particles can be included in the FCC catalyst composition 124, wherein one type of particle includes only nano-ZSM-5 zeolite, and another type of particle includes only USY zeolite.

[0073] Reference again Figure 1, the FCC system 100 includes a fluid catalytic cracking unit 120 and a regenerator 160. In an embodiment, the FCC system 100 may include a plurality of fluid catalytic cracking units 120, which may be operated in series, in parallel, or in a combination of the two. The fluid catalytic cracking unit 120 may include a catalyst-feed mixing zone 128, a cracking reaction zone 122, a catalyst separation zone 130, and a stripping zone (stripping zone) 132. In an embodiment, the cracking reaction zone 122 may be a downflow or "downward" reactor, wherein the reactants flow downward from the catalyst-feed mixing zone 128 through the cracking reaction zone 122 to the separation zone 130. Steam 127 may be introduced into the top portion of the cracking reaction zone 122 to provide additional heating to the mixture of the hydrocarbon feed 102 and the FCC catalyst composition 124.

[0074] It should be understood that Figure 1 The cracking reaction zone 122 of the fluid catalytic cracking unit 120 shown in is a simplified schematic diagram of a specific embodiment of the cracking reaction zone 122 of the fluid catalytic cracking unit, and other configurations of the cracking reaction zone 122 may be suitable for incorporation into the FCC system 100. In an embodiment, the cracking reaction zone 122 may be an upflow cracking reaction zone. In an embodiment, the cracking reaction zone 122 may include one or more riser reactors. Other embodiments may include two or more fluid catalytic cracking units operating in parallel under similar or different operating conditions.

[0075] Reference again Figure 1 , the fluid catalytic cracking unit 120 is fluidly connected to the regenerator 160. In an embodiment, the regenerator 160 can be a single zone regenerator including a regeneration zone 162. The spent FCC catalyst 125 can be regenerated in the regeneration zone 162 to produce a regenerated FCC catalyst 123. In other embodiments, the regenerator 160 can be a dual zone regenerator including two separate regeneration zones (not shown). Again referring to Figure 1 , the regenerator 160 may include a riser 166. The riser 166 may be located between the stripping zone 132 and the regeneration zone 162. The spent FCC catalyst 125 is regenerated to produce a regenerated FCC catalyst 123. The regenerated FCC catalyst 123 is then transferred back to the catalyst-feed mixing zone 128 as the FCC catalyst composition 124.

[0076] The FCC system 100 may include a catalyst hopper 174 disposed between the regeneration zone 162 of the regenerator 160 and the fluid catalytic cracking unit 120. The regenerated FCC catalyst 123 may be transferred from the regeneration zone 162 to the catalyst hopper 174, where the regenerated FCC catalyst 123 may be accumulated and then transferred from the catalyst hopper 174 to the catalyst-feed mixing zone 128 as the FCC catalyst composition 124. The regenerated FCC catalyst 123 may be at an elevated temperature equal to or greater than the reaction temperature in the cracking reaction zone 122, and may provide heat for the endothermic cracking reaction in the cracking reaction zone 122.

[0077] The hydrocarbon feed 102 may be introduced into a catalyst-feed mixing zone 128, where the hydrocarbon feed 102 may be mixed with an FCC catalyst composition 124. The mixture comprising the hydrocarbon feed 102 and the FCC catalyst composition 124 may be introduced into the cracking reaction zone 122. When the cracking reaction zone 122 is a downflow reactor, the mixture of the hydrocarbon feed 102 and the FCC catalyst composition 124 may be introduced into a top portion of the cracking reaction zone 122. When the cracking reaction zone 122 is an upflow reactor, the mixture of the hydrocarbon feed 102 and the FCC catalyst composition 124 may be introduced into the bottom of the riser section of the cracking reaction zone 122, and may be combined with a carrier gas (not shown).

[0078] In embodiments, one or more supplemental feed streams (not shown) may be combined with the hydrocarbon feed 102 prior to introducing the hydrocarbon feed 102 into the catalyst-feed mixing zone 128. In other embodiments, one or more supplemental feed streams may be added directly to the catalyst-feed mixing zone 128, where the supplemental feed streams are mixed with the hydrocarbon feed 102 and the FCC catalyst composition 124 prior to introduction into the cracking reaction zone 122. As previously described, the supplemental feed stream may include one or more of a vacuum residue, tar sands, asphalt, atmospheric residue, vacuum gas oil, demetallized oil, a naphtha stream, or a combination of these.

[0079] During steady-state operation of the FCC system 100, the FCC catalyst composition 124 may be regenerated FCC catalyst 123 transferred from a catalyst hopper 174 to the catalyst-feed mixing zone 128. The catalyst hopper 174 may receive the regenerated FCC catalyst 123 from the regenerator 160 after regeneration of the spent FCC catalyst 125. At the initial startup of the FCC system 100, the FCC catalyst composition 124 may include fresh FCC catalyst (not shown), which may be FCC catalyst composition 124 particulates that have not been circulated through the fluid catalytic cracking unit 120 and the regenerator 160. In an embodiment, fresh FCC catalyst may also be introduced to the catalyst hopper 174 during steady-state operation of the FCC system 100, such that the FCC catalyst composition 124 introduced into the catalyst-feed mixing zone 128 includes a mixture of fresh FCC catalyst and regenerated FCC catalyst 123. During operation, fresh FCC catalyst composition 124 may be periodically introduced into catalyst hopper 174 to replenish lost FCC catalyst composition 124 particulates or to make up for spent FCC catalyst 125 that becomes permanently deactivated (eg, through accumulation of heavy metals in the catalyst).

[0080] The hydrocarbons from the hydrocarbon feed 102 contact the FCC catalyst composition 124 in the cracking reaction zone 122, which causes at least a portion of the hydrocarbons from the hydrocarbon feed 102 to undergo one or more catalytic cracking reactions to form one or more cracking reaction products, which may include one or more olefins. The temperature of the FCC catalyst composition 124 may be equal to or greater than the reaction temperature of the cracking reaction zone 122, and heat may be transferred to the hydrocarbon feed 102 to promote endothermic cracking reactions. Steam 127 may be added to the cracking reaction zone 122 to further increase the temperature in the cracking reaction zone 122, to increase the surface area of ​​the hydrocarbon feed 102 by atomizing the hydrocarbon feed 102 into smaller droplets, or to reduce the hydrocarbon partial pressure, all of which may increase the yield of light olefins compared to not injecting steam into the cracking reaction zone 122.

[0081] In an embodiment, the fluid catalytic cracking unit 120 may operate under high severity reaction conditions. In an embodiment, the cracking reaction zone 122 may operate at a reaction temperature of 580°C to 750°C. In an embodiment, the reaction temperature of the cracking reaction zone 122 can be 580°C to 740°C, 580°C to 720°C, 580°C to 700°C, 580°C to 680°C, 580°C to 660°C, 580°C to 650°C, 600°C to 750°C, 600°C to 740°C, 600°C to 720°C, 600°C to 700°C, 600°C to 680°C, 600°C to 660°C, 600°C to 650°C, 620°C to 750°C, 620°C to 740°C, 620°C to 720°C, 620°C to 700°C, 620°C to 680°C, 620°C to 660°C, or 620°C to 650°C. When the reaction temperature of the cracking reaction zone 122 is above, for example, 750°C, the hydrocarbon feed 102 may undergo increased thermal cracking and decreased catalytic cracking compared to an embodiment in which the reaction temperature of the cracking reaction zone 122 is below 750°C. Thermal cracking of the hydrocarbon feed 102 may increase the yield of ethylene and reduce the yields of other products. In an embodiment, the hydrocarbon feed 102 may contact the FCC catalyst composition 124 in the catalytic cracking unit 120 at a temperature of 600°C to 650°C. Catalytic cracking of the hydrocarbon feed 102 in the fluidized catalytic cracking unit 120 may produce greater amounts of desired products, such as light olefins and aromatic compounds.

[0082] In embodiments, the fluid catalytic cracking unit 120 may be operated at a catalyst to oil weight ratio (CTO) of 2:1 to 10:1, wherein the catalyst to oil weight ratio is the weight ratio of the weight of the FCC catalyst composition 124 to the weight of the hydrocarbon feedstock 102 per unit volume of the reaction mixture comprising the hydrocarbon feedstock 102 and the FCC catalyst composition 124. In embodiments, the fluid catalytic cracking unit 120 may be operated at a catalyst to oil weight ratio of 2:1 to 3:1, 2:1 to 5:1, 2:1 to 10:1, 3:1 to 5:1, or 5:1 to 10:1. Without intending to be bound by any particular theory, it is believed that a catalyst to oil weight ratio of less than 2:1 may not provide a sufficient amount of catalyst to catalytically crack the hydrocarbon feedstock 102 at an economically high yield. It is believed that a catalyst to oil weight ratio greater than 10:1 may not be economically practical for scaling up commercial applications.

[0083] In embodiments, the fluid catalytic cracking unit 120 may be operated with a residence time of 0.1 seconds to 60 seconds. In embodiments, the fluid catalytic cracking unit 120 may be operated with a residence time of 0.1 seconds to 30 seconds, 0.1 seconds to 60 seconds, 20 seconds to 40 seconds, or 30 seconds to 60 seconds. Without intending to be bound by any particular theory, it is believed that a residence time of less than 0.1 seconds does not provide sufficient time for the hydrocarbons in the hydrocarbon feed 102 to be adequately cracked by the FCC catalyst composition 124.

[0084] The hydrocarbon feed 102 is catalytically cracked by contact with the FCC catalyst composition 124 to produce a mixture of spent FCC catalyst 125 and cracking effluent 126. The spent FCC catalyst 125 may be separated from the cracking effluent 126 and passed to a regeneration zone 162 of a regenerator 160, where the spent FCC catalyst 125 is regenerated to produce a regenerated FCC catalyst 123. The regenerated FCC catalyst 123 is then passed back to the cracking reaction zone 122 as the FCC catalyst composition 124.

[0085] After the cracking reaction in the cracking reaction zone 122, the contents of the cracking reaction zone 122 include the spent FCC catalyst 125 and the cracking effluent 126, which can then be transferred to the separation zone 130. In the separation zone 130, the spent FCC catalyst 125 can be separated from at least a portion of the cracking effluent 126. In an embodiment, the separation zone 130 can include one or more gas-solid separators, such as one or more cyclone separators. The spent FCC catalyst 125 discharged from the separation zone 130 can retain at least a portion of the cracking effluent 126, such as the cracking effluent 126 retained in the pores of the spent FCC catalyst 125, the cracking effluent 126 retained between the particles of the spent FCC catalyst 125, or both.

[0086] After separation from the cracked effluent 126 in the separation zone 130, the spent FCC catalyst 125 (which may include at least a portion of the cracked effluent 126 retained in the spent catalytic cracking catalyst 125) may be passed to the stripping zone 132, where the remaining portion of the cracked effluent 126 is stripped from the spent catalyst 125 and recovered as a stripped effluent 134. The stripped effluent 134 may be passed to one or more downstream unit operations, or combined with the cracked effluent 126 for further processing. Steam 133 may be introduced into the stripping zone 132 to facilitate stripping of the retained portion of the cracked effluent 126 from the spent FCC catalyst 125. The stripped effluent 134 (which may include at least a portion of the steam 133 introduced into the stripping zone 132) may be discharged from the stripping zone 132, at which point the stripped effluent 134 may pass through a cyclone separator (not shown) and exit a stripper vessel (not shown). The stripped effluent 134 may be directed to one or more product recovery systems according to methods known in the art. The stripped effluent 134 may also be combined with one or more other streams, such as the cracked effluent 126. After the spent FCC catalyst 125 is stripped of at least a portion of the retained portion of the cracked effluent 126, the spent FCC catalyst 125 may then be passed to the regeneration zone 162 of the regenerator 160.

[0087] The spent FCC catalyst 125 and the combustion gas 170 may be introduced into the bottom end of the riser 166 of the regenerator 160. The combustion gas 170 may include one or more of combustion air, oxygen, fuel gas, fuel oil, or a combination of these. The combustion gas 170 may transport the spent FCC catalyst 125 upwardly to the regeneration zone 162 through the riser 166, where the coke deposits and other residual hydrocarbons are at least partially oxidized (combusted). The coke deposited on the spent FCC catalyst 125 in the cracking reaction zone 122 may begin to oxidize in the presence of the combustion gas 170 in the riser 166 on the way up to the regeneration zone 162. The spent FCC catalyst 125 is regenerated to produce a regenerated FCC catalyst 123. During the regeneration process, the coke deposits on the spent FCC catalyst 125 are removed, and the catalyst particles are heated by burning the coke deposits, additional fuel gas, or a combination of these to produce a regenerated FCC catalyst 123. The regenerated FCC catalyst 123 is then transferred back to the cracking reaction zone 122 as the FCC catalyst composition 124 .

[0088] As previously mentioned, embodiments of the present disclosure include contacting hydrocarbon feed 102 with FCC catalyst composition 124, FCC catalyst composition 124 includes nano-ZSM-5 zeolite impregnated with phosphorus, USY zeolite impregnated with lanthanum oxide, alumina binder, colloidal silica and a matrix material comprising kaolin. Comprising two or more different zeolite components can improve the selectivity and yield of FCC process, to produce light olefins in the whole range of some unconventional hydrocarbon feeds (such as crude oil) for fluid catalytic cracking process. Compared with conventional FCC catalyst, FCC catalyst composition 124 can be particularly suitable for catalytic cracking crude oil under high severity reaction conditions, to produce higher olefin yield. Not subject to any particular theory, it is believed that different zeolite components can have enough activity to promote the catalytic cracking of lighter hydrocarbons, and are gentle enough to avoid excessive catalytic cracking, such as the continuous cracking of light olefins and light aromatic product compounds. The balanced activity provided by the mixture of zeolite components can enhance the yield of products (eg, light olefins) from the catalytic cracking of light and heavy hydrocarbons present in crude oil.

[0089] In addition, embodiments of the present disclosure can provide a catalyst with reduced deactivation rate in the catalytic cracking process of crude oil added directly to the FCC system. The reduced deactivation rate of the catalyst can improve the economics of catalytic cracking crude oil to form light olefins, among other features.

[0090] Example

[0091] Various aspects of the present disclosure will be further illustrated by the following examples. These examples are illustrative in nature and should not be construed as limiting the subject matter of the present disclosure. In the examples, nano-ZSM-5 zeolite and FCC catalyst compositions according to the present disclosure were prepared. The materials for preparing the nano-ZSM-5 zeolite of Example 1 and the FCC catalyst compositions of Example 2 are provided in the following table 2.

[0092] Table 2

[0093]

[0094] Example 1: Synthesis of Nano-ZSM-5 Zeolite

[0095] To prepare the nano-ZSM-5 zeolite of Example 1, 40 grams (g) of a precursor solution was prepared by mixing water, colloidal silica, sodium hydroxide, tetrapropylammonium hydroxide (TPAOH), and aluminum isopropoxide (Al(OI-Pr)3) according to the molar ratios (mol / mol) in Table 3. The precursor solution was stirred at room temperature for one day, transferred to a stainless steel autoclave with a Teflon line, heated to 140°C, and then maintained at 140°C for 4 days to obtain a product solution. The product solution was centrifuged, and the solid product was collected. The solid product was dispersed in deionized water and centrifuged to obtain a washed product. The washed product was dried in an oven at 80°C. The washed product was calcined using the following procedure: heating at a rate of 3°C / min until a temperature of 200°C was reached, maintaining the temperature for two hours, heating at a rate of 3°C / min until a temperature of 550°C was reached, and maintaining the temperature for 8 hours to produce the nano-ZSM-5 zeolite of Example 1. The average particle size of the nano-ZSM-5 zeolite was 0.084 μm as determined by electron microscopy. The average silica to alumina ratio of the nano-ZSM-5 zeolite was 33 and the average surface area was 379 m 2 / g, and the average total pore volume per unit weight is 0.254 cm 3 / g.

[0096] Table 3

[0097]

[0098] Example 2: Preparation of FCC catalyst composition

[0099] To prepare the FCC catalyst composition of Example 2, the nano-ZSM-5 zeolite of Example 1 was combined and impregnated with 7.5 wt % phosphorus pentoxide, and USY zeolite (CBV-780 commercially available from Zeolyst International) was impregnated with 2.5 wt % lanthanum oxide. The USY zeolite had an average total pore volume per unit weight of 0.486 cm 3 / g. Nano-ZSM-5 zeolite impregnated with phosphorus pentoxide and USY zeolite impregnated with lanthanum oxide were mixed with water, alumina binder, colloidal silica and kaolin to produce a mixture. The mixture was stirred for 1 hour, and the resulting slurry was placed in a programmed temperature oven for drying and calcination to produce FCC catalyst composition particles. The FCC catalyst composition particles were ground into fine powder by a mortar and pestle. Then, the ground FCC catalyst composition particles were screened into a fraction between 40 microns and 120 microns (um) and used for characterization and evaluation. The composition of the FCC catalyst composition particles of Example 2 is provided in Table 4.

[0100] Table 4

[0101]

[0102]

[0103] Example 3: Evaluation of the FCC Catalyst Composition of Example 2

[0104] In Example 3, the performance of the FCC catalyst composition of Example 2 in cracking Arab light crude oil under various reaction conditions was evaluated. The properties of the Arab light crude oil used in the example are shown in Table 1 above. The Arab Light (AL) crude oil was catalytically cracked using the FCC catalyst composition of Example 1 in a Sakuragi Rikagaku (Japan) Micro Activity Test (MAT) instrument using a quartz tubular reactor. The FCC catalyst composition of Example 2 was evaluated for cracking Arab light crude oil according to standard test method ASTM D-3907. Prior to the evaluation, the FCC catalyst composition was steamed at 810°C for 6 hours and then subjected to cracking reactions. The experiment was conducted in a MAT unit with a time-on-stream (TOS) of 30 seconds. The cracking reactions were conducted at temperatures of 600°C, 625°C, and 650°C, with a catalyst to oil weight ratio of about 5.5 and about 9.8.

[0105] After each reaction, the FCC catalyst composition particles were stripped using nitrogen (N2) at a flow rate of 30 milliliters per minute (mL / min). The liquid product was collected in a liquid receiver, and the gaseous product was collected in a gas burette by water displacement and sent to a gas chromatograph (GC) for analysis. The amount of coke produced by the reaction was measured using the spent catalyst.

[0106] Table 5 shows the MAT results for cracking AL crude oil on the FCC catalyst composition of Example 2. It can be seen that a high light olefin yield of greater than 32 wt% is obtained using the FCC catalyst composition of Example 2. The reaction conditions of 650°C and a catalyst to oil ratio of 5.46 achieved a light olefin yield of 35.98 wt% (Example 3-3). The reaction conditions of 625°C and a catalyst to oil ratio of 9.79 achieved a light olefin yield of 36.18 wt% (Example 3-4).

[0107] Table 5

[0108]

[0109]

[0110] As shown in Table 5, increasing the catalyst to oil ratio at a fixed temperature results in an increase in propylene yield (C3=) and total light olefin yield, with a catalyst to oil ratio of up to about 9. At a fixed catalyst to oil ratio, increasing the reaction temperature from 600°C to 625°C results in an increase in propylene, ethylene, and light olefin yields. However, increasing the reaction temperature from 625°C to 650°C only results in a slight increase in propylene yield and a slight increase in light olefin yield. In addition, increasing the reaction temperature from 625°C to 650°C results in an increase in ethylene yield. At temperatures above 650°C, it is believed that an increase in thermal cracking reduces propylene yield and increases ethylene yield, as shown by the trend of ethylene increase when the temperature increases from 625°C to 650°C. At temperatures below 600°C, emphasis is placed on the production of gasoline components, and the yield of light olefins is lower.

[0111] Comparative Example 4: Evaluation of Comparative FCC Catalyst Compositions

[0112] In Comparative Example 4, the performance of a commercial FCC catalyst composition for cracking Arabian light crude oil at a reaction temperature of 625°C and a catalyst to oil ratio of about 9 was evaluated. Comparative Example 4-1 used a ZSM-5 zeolite available from GRACE as Olefins Ultrara. Comparative Example 4-2 used Ecat based on Y-type zeolite. Comparative Example 4-3 used Ecat based on ZSM-5 and Y zeolites. As described in Example 3, the commercial FCC catalyst composition of Comparative Example 4 was used to catalytically crack Arabian light (AL) crude oil. Table 6 shows the MAT results for cracking AL crude oil on the commercial FCC catalyst composition of Comparative Example 4.

[0113] Table 6

[0114]

[0115]

[0116] As shown in Table 6, under similar conditions, the yields of propylene and total light olefins using Example 3 (Example 3-4) are greater than the yields of propylene and total light olefins using the catalyst of Comparative Example 4. In addition, the catalyst in Example 3-4 produces the best coke formation and less dry gas compared to the catalyst of Comparative Example 4.

[0117] Example 5: Estimation of Catalyst Deactivation of the FCC Catalyst Composition of Example 1

[0118] In Example 5, the deactivation rate of the FCC catalyst composition of Example 2 is estimated. In industry, FCC catalyst deactivation is evaluated based on the content of nickel (Ni) and vanadium (V) accumulated on the equilibrium catalyst (E-Cat). The catalyst can be considered as E-Cat after circulating between the regenerator and the FCC reactor for several days of continuous operation. The deactivation of catalytic cracking catalysts is mainly contributed by two factors, namely steam and feed contaminants. In industry, the deactivation of FCC catalysts is evaluated by taking out E-Cat samples from the FCC system and analyzing the Ni and V content in the samples. In the above Example 3, the FCC catalyst composition passed through the MAT unit once and may not fully represent the industrial E-Cat. Alternatively, the FCC catalyst composition of Example 2 is steam deactivated at 810°C for 6 hours and can therefore be considered to be representative of the industrial E-Cat.

[0119] In addition to the steam-deactivated catalyst, an equation based on the metal balance around the unit (input metal amount - output metal amount = accumulated metal) in the literature is used to estimate how much Ni and V accumulate on the FCC catalyst combination of Example 1 at equilibrium. For example, Fluid Catalytic Cracking Handbook, 4th Edition, Sadeghbeigi, 2020 provides equations for estimating Ni and V accumulation on FCC catalysts. These equations estimate the Ni and V content on E-Cat based on the nickel and vanadium levels in the feed (AL crude oil in these examples) and the daily catalyst addition rate. Solving for C a M e The first-order differential equation (Equation 1) is as follows:

[0120]

[0121] in:

[0122] M e = E-cat metal content, parts per million by weight (ppmw);

[0123] A=(W x M f ) / C a ;

[0124] W = feed rate, pounds per day (lbs / day);

[0125] M f = feed metal, ppmw;

[0126] C a = catalyst addition rate, lb / day;

[0127] M0 = initial metal on E-cat, ppmw;

[0128] Τ = time, days;

[0129] I = catalyst inventory, pounds (lbs); and

[0130] B = catalyst addition rate, pounds of catalyst per barrel of feed, where one barrel equals 42 U.S. gallons.

[0131] At steady state, the concentration of any metal on the catalyst is approximately calculated using the following equation (Equation 2):

[0132] M e =((141.5 / (131.5+°API 进料 )x 350.4x M f ) / B(Equation 2)

[0133] Among them, °API 进料 Equal to the API gravity of the feed, degrees.

[0134] After executing these equations above, it was found that the Ni and V in the FCC catalyst composition of Example 2 calculated at equilibrium were less than half of the minimum amount of catalyst to be considered as spent / deactivated in E-Cat. Specifically, the sum of Ni and V should be about 10,000 ppm on E-Cat, which is considered as a spent catalyst. The amount of Ni+V calculated for Example 2 was 4969 ppm. In contrast, the calculated Ni+V for E-Cat FCC was 4086 ppm. E-Cat was used for operation of cracking a feed with 10 ppm of Ni+V, while the FCC catalyst composition of Example 1 was used to crack AL crude oil with about 13 ppm of Ni+V. The Ni+V of Example 1 and the Ni+V of the comparative E-Cat were calculated using the same catalyst addition rate. Although Equation 1 does not take into account the size of the zeolite, it is believed that the smaller size of the nano-ZSM-5 zeolite provides a shorter path for hydrocarbons to reach the catalyst than the ZSM-5 zeolite with an average particle size greater than 0.2 μm. Therefore, it is believed that the nano-ZSM-5 zeolite can accumulate less Ni and V than the ZSM-5 zeolite having an average particle size greater than 0.2 μm.

[0135] The first aspect of the present disclosure relates to a method for converting crude oil into light olefins, aromatic compounds, or both, the method comprising contacting the crude oil with a fluidized catalytic cracking (FCC) catalyst composition in an FCC system at a temperature greater than or equal to 580° C., the weight ratio of the FCC catalyst composition to the crude oil being 2:1 to 10:1, and the residence time being 0.1 to 60 seconds. The FCC catalyst composition comprises an ultrastable Y-type zeolite (USY zeolite) impregnated with lanthanum, a nano-ZSM-5 zeolite impregnated with phosphorus, an alumina binder, colloidal silica, and a matrix material comprising kaolin. The nano-ZSM-5 zeolite has an average particle size of 0.01 μm to 0.2 μm. The contact causes at least a portion of the hydrocarbons in the crude oil to undergo a cracking reaction to produce a cracking effluent comprising at least olefins.

[0136] A second aspect of the disclosure may include the first aspect, wherein the FCC catalyst composition comprises 10 wt% to 30 wt% of USY zeolite impregnated with lanthanum.

[0137] A third aspect of the present disclosure may include any of the first or second aspects, wherein the FCC catalyst composition comprises 10 wt% to 30 wt% of the nano-ZSM-5 zeolite impregnated with phosphorus.

[0138] A fourth aspect of the present disclosure may include any one of the first to third aspects, wherein the USY zeolite is impregnated with 1 wt % to 5 wt % of lanthanum oxide based on the total weight of the USY zeolite.

[0139] A fifth aspect of the present disclosure may include any one of the first to fourth aspects, wherein the nano-ZSM-5 zeolite is impregnated with 1 wt % to 15 wt % of phosphorus pentoxide based on the total weight of the nano-ZSM-5 zeolite.

[0140] A sixth aspect of the present disclosure may include any one of the first to fifth aspects, wherein the FCC catalyst composition comprises 21 wt% USY zeolite impregnated with lanthanum, 20 wt% nano-ZSM-5 zeolite impregnated with phosphorus, 8 wt% alumina binder, 49 wt% kaolin, and 2 wt% colloidal silica, wherein the weight percentages are based on the total weight of the FCC catalyst composition.

[0141] A seventh aspect of the present disclosure may include any one of the first to sixth aspects, wherein the crude oil has an American Petroleum Institute gravity of 15 degrees to 50 degrees;

[0142] An eighth aspect of the present disclosure may include any one of the first to seventh aspects, wherein the crude oil has a density greater than 0.8 g / ml at 15°C.

[0143] A ninth aspect of the present disclosure may include any one of the first to eighth aspects, wherein the crude oil has an initial boiling point of 30°C to 50°C and a final boiling point greater than 720°C.

[0144] A tenth aspect of the present disclosure may include any one of the first to ninth aspects, wherein at least 50 weight % of the crude oil has a boiling temperature greater than or equal to 300°C.

[0145] An eleventh aspect of the present disclosure may include any one of the first to tenth aspects, wherein the crude oil has a concentration of paraffin compounds of less than 50 weight % per unit weight of the crude oil.

[0146] A twelfth aspect of the present disclosure may include any one of the first to eleventh aspects, wherein the crude oil has a concentration of aromatic compounds greater than or equal to 20 weight % per unit weight of the crude oil.

[0147] A thirteenth aspect of the present disclosure may include any one of the first to twelfth aspects, wherein the crude oil has a concentration of cycloalkanes greater than or equal to 25 weight % per unit weight of the crude oil.

[0148] A fourteenth aspect of the present disclosure may include any one of the first to thirteenth aspects, wherein the crude oil is Arabian light crude oil.

[0149] A fifteenth aspect of the present disclosure may include any one of the first to fourteenth aspects, wherein the crude oil is contacted with the FCC catalyst composition at a temperature of 600°C to 650°C.

[0150] A sixteenth aspect of the present disclosure may include any one of the first to fifteenth aspects, wherein the crude oil is contacted with the FCC catalyst composition for a residence time of 20 seconds to 40 seconds.

[0151] A seventeenth aspect of the present disclosure may include any one of the first to sixteenth aspects, wherein the FCC unit is a downflow FCC unit.

[0152] An eighteenth aspect of the present disclosure may include any one of the first to seventeenth aspects, wherein the crude oil has a final boiling point greater than 720°C.

[0153] A nineteenth aspect of the present disclosure may include any one of the first to eighteenth aspects, wherein the FCC catalyst composition comprises a plurality of catalyst particles, wherein each of the plurality of catalyst particles comprises the nano-ZSM-5 zeolite impregnated with phosphorus, the USY zeolite impregnated with lanthanum, the alumina binder, the kaolin, and the colloidal silica.

[0154] A twentieth aspect of the present disclosure may include any one of the first to nineteenth aspects, wherein the crude oil has a boiling point temperature of 50 wt % of greater than or equal to 350° C. to less than or equal to 400° C.

[0155] A twenty-first aspect of the present disclosure may include any one of the first to twentieth aspects, wherein the crude oil is whole crude oil.

[0156] The twenty-second aspect of the present disclosure may include any one of the first to twenty-first aspects, wherein the FCC catalyst composition comprises: 20 wt% of the nano-ZSM-5 zeolite based on the total weight of the FCC catalyst composition, 21 wt% of the USY-type zeolite based on the total weight of the FCC catalyst composition, 8 wt% of alumina binder based on the total weight of the FCC catalyst composition, 49 wt% of kaolin based on the total weight of the FCC catalyst composition, and 2 wt% of colloidal silica based on the total weight of the FCC catalyst composition. The nano-ZSM-5 zeolite is impregnated with 7.5 wt% of P2O5 based on the total weight of the nano-ZSM-5 zeolite. The USY-type zeolite comprises 2.5 wt% of lanthanum oxide (La2O3) based on the total weight of the USY-type zeolite.

[0157] A twenty-third aspect of the present disclosure may relate to an FCC catalyst composition comprising an ultrastable Y-type zeolite (USY zeolite) impregnated with lanthanum, a nano-ZSM-5 zeolite impregnated with phosphorus (wherein the nano-ZSM-5 zeolite has an average particle size of 0.01 μm to 0.2 μm), an alumina binder, colloidal silica, and a matrix material comprising kaolin.

[0158] The twenty-fourth aspect of the present disclosure may include the twenty-third aspect, wherein the FCC catalyst composition comprises: 20 wt% of the nano-ZSM-5 zeolite based on the total weight of the FCC catalyst composition, 21 wt% of the USY type zeolite based on the total weight of the FCC catalyst composition, 8 wt% of alumina binder based on the total weight of the FCC catalyst composition, 49 wt% of kaolin based on the total weight of the FCC catalyst composition, and 2 wt% of colloidal silica based on the total weight of the FCC catalyst composition. The nano-ZSM-5 zeolite is impregnated with 7.5 wt% of P2O5 based on the total weight of the nano-ZSM-5 zeolite. The USY type zeolite comprises 2.5 wt% of lanthanum oxide (La2O3) based on the total weight of the USY type zeolite.

[0159] It is worth noting that any two quantitative values ​​assigned to an attribute may constitute a range for that attribute, and all combinations of ranges formed by all specified quantitative values ​​for a given attribute are contemplated in this disclosure.

[0160] It is noted that one or more of the following claims utilize the term "wherein" as a transitional phrase. For the purpose of defining the present technology, it is noted that this term is introduced in the claims as an open transitional phrase to introduce a series of features of the structure and should be interpreted in a similar manner to the more commonly used open-ended term "comprising".

[0161] Having described the subject matter of the present disclosure in detail and with reference to specific aspects, it is noteworthy that the various details of these aspects should not be considered to imply that these details are essential components of these aspects. Rather, the claims appended hereto should be considered as the only representation of the breadth of the present disclosure and the corresponding scope of the various aspects described in the present disclosure. In addition, it is apparent that modifications and variations are possible without departing from the scope of the appended claims.

Claims

1. A method for converting crude oil to light olefins, aromatic compounds, or both, the method comprising contacting the crude oil with a fluidized catalytic cracking (FCC) catalyst composition in an FCC system at a temperature greater than or equal to 580° C., the weight ratio of the FCC catalyst composition to the crude oil being from 2:1 to 10:1, and the residence time being from 0.1 seconds to 60 seconds, wherein: The FCC catalyst composition comprises: Ultrastable Y zeolite (USY zeolite) impregnated with lanthanum; A nano-ZSM-5 zeolite impregnated with phosphorus, wherein the nano-ZSM-5 zeolite has an average particle size of 0.01 μm to 0.2 μm; Alumina binder; Colloidal silicon dioxide; and a matrix material comprising kaolin; and The contacting causes at least a portion of the hydrocarbons in the crude oil to undergo a cracking reaction to produce a cracking effluent comprising at least olefins.

2. The method according to claim 1, wherein: The FCC catalyst composition comprises 10 wt% to 30 wt% of USY zeolite impregnated with lanthanum; The FCC catalyst composition comprises 10 wt% to 30 wt% of a nano-ZSM-5 zeolite impregnated with phosphorus; or both.

3. The method according to claim 1, wherein: The USY zeolite is impregnated with 1 wt % to 5 wt % of lanthanum oxide based on the total weight of the USY zeolite.

4. The method according to claim 1, wherein: The nano-ZSM-5 zeolite is impregnated with 1 wt % to 15 wt % of phosphorus pentoxide based on the total weight of the nano-ZSM-5 zeolite.

5. The method according to claim 1, wherein: The FCC catalyst composition comprises 21 wt% USY zeolite impregnated with lanthanum, 20 wt% nano-ZSM-5 zeolite impregnated with phosphorus, 8 wt% alumina binder, 49 wt% kaolin and 2 wt% colloidal silica, wherein the weight percentages are based on the total weight of the FCC catalyst composition.

6. The method according to claim 1, wherein: The crude oil has: API gravity from 15 to 50 degrees; Density greater than 0.8 g / ml at 15°C.

7. The method according to claim 1, wherein: The crude oil has an initial boiling point of 30°C to 50°C, and a final boiling point of greater than 720°C.

8. The method according to claim 1, wherein: At least 50% by weight of the crude oil has a boiling temperature greater than or equal to 300°C.

9. The method according to claim 1, wherein: The crude oil has: Paraffin compounds in a concentration of less than 50% by weight per unit weight of said crude oil; Aromatic compounds in a concentration greater than or equal to 20 weight percent per unit weight of said crude oil; cycloalkanes at a concentration greater than or equal to 25 weight percent per unit weight of said crude oil; or a combination thereof.

10. The method according to claim 1, wherein: The crude oil is: All crude oil; Arabian Light Crude Oil; or both.

11. The method according to claim 1, wherein: The crude oil is contacted with the FCC catalyst composition at a temperature of 600° C. to 650° C.; The crude oil is contacted with the FCC catalyst composition for a residence time of 20 seconds to 40 seconds; Or the crude oil is contacted with the FCC catalyst composition at a temperature of 600° C. to 650° C. for a residence time of 20 seconds to 40 seconds.

12. The method according to claim 1, wherein: The FCC unit is a downflow FCC unit.

13. The method according to claim 1, wherein: The FCC catalyst composition comprises a plurality of catalyst particles, wherein each of the plurality of catalyst particles comprises the nano-ZSM-5 zeolite impregnated with phosphorus, the USY zeolite impregnated with lanthanum, the alumina binder, the kaolin, and the colloidal silica.

14. An FCC catalyst composition for producing olefins and aromatic compounds from crude oil, the FCC catalyst composition comprising: Ultrastable Y zeolite (USY zeolite) impregnated with lanthanum; A nano-ZSM-5 zeolite impregnated with phosphorus, wherein the nano-ZSM-5 zeolite has an average particle size of 0.01 μm to 0.2 μm; Alumina binder; Colloidal silicon dioxide; and A matrix material comprising kaolin.

15. The composition of claim 14, wherein the FCC catalyst composition comprises: 20 wt% of nano-ZSM-5 zeolite based on the total weight of the FCC catalyst composition, wherein impregnating the nano-ZSM-5 zeolite with 7.5 wt % of P2O5 based on the total weight of the nano-ZSM-5 zeolite; 21 wt% of a USY-type zeolite based on the total weight of the FCC catalyst composition, wherein the USY-type zeolite comprises 2.5 wt% of lanthanum oxide (La2O3) based on the total weight of the USY-type zeolite; 8 wt % of an alumina binder, based on the total weight of the FCC catalyst composition; 49 wt% kaolin, based on the total weight of the FCC catalyst composition; and 2 wt% colloidal silica based on the total weight of the FCC catalyst composition.